Análise do impacto de infecções por parasitos intestinais e por Schistosoma mansoni no desempenho cognitivo e na interação entre sistema hormonal e sistema imunológico em escolares - Mauricio da Silva Guedes (2016)
Intestinal parasites and schistosomiasis still cause serious public health problems and are distributed all over the world. Highest prevalences are found in under-developed countries with inferior economical conditions, sanitation and educational level. Generally, these diseases are associated with undernutrition and anemia and result in decreased physical and cognitive development in children, which are most affected. Especially in schoolchildren, there exists an increasing frequency of intestinal parasites and schistosome infections. Up to now, very few studies have evaluated the impact of such infections on the cognitive development or capacity.Therefore, the goal of the present investigation was to evaluate the impact of intestinal parasitism on cognition and on the interaction between hormonal and immune system in schoolchildren from the Municipality of Jaboticatubas, Minas Gerais State. A total of 316 schoolchildren participated during the initial parasitological exams. Of those, fifty-three individuals participated in the cohort study. Apart from parasitological exams, immunological parameters, hormone levels, and the cognitive performance were evaluated, the later using Cubes and Vocabulary subtests of Wechsler Intelligence Scale for Children WISC. Statistical analyses were performed using BioEstat 5.3 version. The significance level was set to p 0.05. For parametric data, Students t-test and correlation of Pearson were applied. For non-parametric data, Wilcoxon or Mann- Whitney U-test were used and correlations were evaluated by using Spearmans rank test. An overall prevalence of 8.9% for intestinal parasitism and/or schistosomiasis resulted in examined schoolchildren. Out of these infected individuals, the majority (71.4%) were mono- or co-infected with S. mansoni. Analyses of immune responses revealed an increase of immunological markers, such as IL-1, TNF- and IL-12 in S. mansoni infected schoolchildren. Thus, indicating a predominant inflammatory or type 1 immune response in this group. This immunological profile is accompanied by increased melatonin levels, a hormone which is known to increase IL-12 production. Three months after anti-parasitic treatment, a significant increase in IL-8 production was measured, which might be a response against the liberation of parasite antigens after disintegration of adult parasites of S. mansoni in the portal system or mesenteric veins. Evaluation of the cognitive capacity of infected children did not reveal improvement after chemotherapy and no significant differences between the study groups were notified. Within the infected group, there was a positive association between the Cubes subtest and the secretion of two cytokines (IL-27 and IL-33). After treatment, a positive correlation between Cubes subtest and TNF-; and between Vocabulary subtest and the cytokines IL-1 and TNF- resulted. Though, we found immunological and hormonal changes in infected schoolchildren before and three months after chemotherapy, we were not able, to find an impact of intestinal infections and/or schistosomiasis on the cognitive function of these schoolchildren. Most probably, this lacking impact on cognition was due to low parasite loads in the endemic population. Even though, chemotherapy did not result in improved cognitive functions in schoolchildren, we were able to show the viability of the theoretical concept and of the applied methods, which may be further improved in future studies with parasitezed schoolchildren